Clinical value of additional resection of a margin‐positive distal bile duct in perihilar cholangiocarcinoma. Issue 6 (19th March 2019) - Otsuka, S.; Ebata, T.; Yokoyama, Y.; Mizuno, T.; Tsukahara, T.; Shimoyama, Y.; Ando, M.; Nagino, M.
Abstract : Background: Little is known about the effect of additional resection for a frozen‐section‐positive distal bile duct margin (DM) in perihilar cholangiocarcinoma. Methods: Patients who underwent surgical resection for perihilar cholangiocarcinoma between 2001 and 2015 were analysed retrospectively, focusing on the DM. Results: Of 558 consecutive patients who underwent frozen‐section examination for a DM, 74 (13·3 per cent) had a frozen‐section‐positive DM with invasive cancer or carcinoma in situ . Eventually, 53 patients underwent additional resection (bile duct resection in 44 and pancreatoduodenectomy in 9), whereas the remaining 21 patients did not. Ultimately, R0 resection was achieved in 30 of the 53 patients (57 per cent). No patient who underwent additional resection died from surgical complications. The 44 patients with additional bile duct resection had a 5‐year overall survival rate of 31 per cent. Overall survival of the nine patients who had pancreatoduodenectomy was better, with a 10‐year rate of 67 per cent. Survival of the 21 patients without additional resection was dismal: all died within 5 years. Multivariable analyses identified nodal status and additional resection as independent prognostic factors (lymph node metastasis: hazard ratio (HR) 2·26, 95 per cent c.i. 1·26 to 4·07; bile duct resection versus no additional resection: HR 0·32, 0·17 to 0·60; pancreatoduodenectomy versus no additional resection: HR 0·08, 0·02 to 0·29). Conclusion: Additional resection for frozen‐section‐positive DM in perihilar cholangiocarcinoma frequently yields R0 margins. It offers a better chance of long‐term survival, and thus should be performed in carefully selected patients. Abstract : The clinical value of additional resection for frozen‐section‐positive distal bile duct margin was evaluated in patients who underwent resection for perihilar cholangiocarcinoma. Additional bile duct resection or pancreatoduodenectomy frequently yields R0 margins, offers a better chance of long‐term survival, and thus should be performed in carefully selected patients. Additional resection adds value